Venture capital, innovation activities, and economic growth: are feedback effects at work?. Issue 2 (3rd April 2017) - Pradhan, Rudra P.; Maradana, Rana Pratap; Dash, Saurav; Zaki, Danish B.; Gaurav, Kunal; Jayakumar, Manju
Abstract: This study makes an attempt to assess the relationship between venture capital, innovation activities and per capita economic growth in the European Economic Area (EEA) countries between 1989 and 2014. We use three indicators of venture capital and eight activities of innovation to examine this assessment. The study principally highlights whether Granger causality runs between these variables both ways, one way, or not at all. Using a panel vector error correction model (VECM), we find that both venture capital and innovation activities contribute to long-run per capita economic growth. These results provide imperative policy implications for these EEA countries.